Single Step Synthesis and Characterisation of Nanocrystalline Cobalt Ferrite by Auto-Combustion Method. (2015) - Shanmugavel, T.; Raj, S. Gokul; Rajarajan, G.; Kumar, G. Ramesh; Boopathi, G.
Abstract: Nano-Crystalline cobalt ferrite nanoparticles were synthesized from an aqueous solution containing metal nitrates and citric acid as a capping agent by an auto-combustion method followed by calcined at high temperature at 600 °C. The structural characteristics and single phase formation of the calcined sample is determined by X-ray diffraction (XRD). Magnetization measurements were obtained at room temperature by using a vibrating sample magnetometer (VSM), which showed that the calcined sample exhibited typical magnetic behaviour.